STUDY OF NEPETAE CATARIAE HERBA FRUITS AS PROMISING MEDICINAL PLANT RAW MATERIAL - A. G. Devyatov; G. S. Lapshin; E. Yu. Babaeva; E. A. Motina; E. V. Zvezdina; V. V. Vandishev (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2019)
Nepetae catariae herba is used in the Russian Federation as spice. The chemical compounds of herb have been studied. This plant has been introduced into the culture. There are its domestic varieties. The fruits of the plant accumulate up to 25% of fatty oil and contain specific laballenic acid, which has a wide range of antimicrobial and fungicidal actions. The yield of fruit crops is 5-6 c/ha.The aim is to study some criteria for the standardization of the quality of Nepetae catariae herb as a new medicinal plant raw material.Materials and methods. The studied fruits are from the biological collection of Federal State Budgetary Institution of All - Russia Research Institute of Medicinal and Aromatic Plants. Binocular magnifier brand MBS-10 and Axioplan 2 imaging microscope by Carl Zeiss were used. The sample preparation was carried out according to the State Pharmacopoeia of the Russian Federation (XIV edition). Anatomical diagnostic features were studied in powder and cross section with staining reagents for the presence of some biologically active substances. Qualitative reactions were carried out with water and alcohol-water extracts from the fruits. The content of the lipid complex according to pharmacopoeia monograph 2.5.0035.15 has been determined.Results. A description of the external and diagnostic anatomical features is given. The main groups of biologically active substances and the content of the lipid complex in a possible new material - the fruits of Nepeta cataria - have been identified.Conclusion. The description of the external features of the fruit has been specified. For the first time, crushed fruits have been characterized. It has been established that the morphology of endocarp cells and seed embryo cells are best preserved in a mellow fruit. Physico-optical properties of cellular structures and the ability for basic microchemical reactions are preserved in all zones of pericarp and seeds. Qualitative reactions showed the presence of the following components in the fruits: saponins, flavonoids and a lipid complex. A dispersion composition has been studied. The yield of the lipid complex and its appearance have been determined. Fruits can be used as promising fat-oil raw materials. The results of the study can be used in drafting Pharmacovigilance Reference Document considering a promising type of medicinal plant raw material on the basis of Nepetae catariae herba fruits.